2011
DOI: 10.1002/cmdc.201100037
|View full text |Cite
|
Sign up to set email alerts
|

The Approach of Conformational Chimeras to Model the Role of Proline‐Containing Helices on GPCR Mobility: the Fertile Case of Cys‐LTR1

Abstract: The homology modeling of GPCRs has benefitted vastly from the availability of some resolved structures, which allow the generation of many reliable GPCR models. However, the dynamic behavior of such receptors has been only minimally examined in silico, although several pieces of evidence have highlighted some conformational switches that can orchestrate the activation mechanism. Among such switches, Pro-containing helices play a key role in determining bending in TM helices and thereby the width of the TM bund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 58 publications
(64 reference statements)
0
17
0
Order By: Relevance
“…These two distributions are very similar. There are a similar number of helices with maximum angles <20 in the two datasets, and the two distributions peak at the same angle (10 ). A few more membrane helices than soluble helices have angles between 20 and 30 , and a few more soluble helices than membrane helices have maximum angles above 50 .…”
Section: Angle Distributionsmentioning
confidence: 81%
See 1 more Smart Citation
“…These two distributions are very similar. There are a similar number of helices with maximum angles <20 in the two datasets, and the two distributions peak at the same angle (10 ). A few more membrane helices than soluble helices have angles between 20 and 30 , and a few more soluble helices than membrane helices have maximum angles above 50 .…”
Section: Angle Distributionsmentioning
confidence: 81%
“…Disruptions of α‐helices (frequently referred to as kinks) are known to occur in many proteins . It has been claimed that these are much less frequent in soluble protein helices than membrane protein helices, and that those in transmembrane helices are linked to function . The majority of previous research has concentrated on kinks in transmembrane helices, but there is little comparable research into soluble helix kinks.…”
Section: Introductionmentioning
confidence: 99%
“…4351 They offer a way to sample different functional substates of the GPCRs 40,52,53 and for the rationalization of its ligand binding and functional effects. 39,5460 However, when using this approach, one is often unsure of the relevance of all the substates sampled. To help prioritize the analysis of the sampled substates, we developed a new protein pairwise similarity method (ProS) to compare and visualize the structural data generated in an MD run and to cluster the GPCR substructures sampled.…”
mentioning
confidence: 99%
“…In a recent study, we showed that the structural effects of the Pro‐containing transmembrane helices can be simulated by generating the so‐called conformational chimeras, namely GPCR models in which the possible conformations of the Pro‐containing helices are exhaustively combined. These chimeras were found to account for receptor flexibility and were applied to explore ligand recognition by the human Cys‐LTR1 receptor 7…”
Section: Introductionmentioning
confidence: 99%